Microtubule-based perception of mechanical conflicts controls plant organ morphogenesis - Stöckle, Dorothee; Reyes-Hernández, Blanca Jazmin; Vicles Barro, Amaya; Nenadić, Milica; Winter, Zsofiá; Marc-Martin, Sophie; Bald, Lotte; Ursache, Robertas; Fujita, Satoshi; Maizel, Alexis; Vermeer, Joop (My University, 2022)
Precise coordination between cells and tissues is essential for differential growth in plants. During lateral root formation in Arabidopsis thaliana, the endodermis is actively remodeled to allow outgrowth of the new organ. Here, we show that microtubule arrays facing lateral root founder cells display a higher order compared to arrays on the opposite side of the same cell, and this asymmetry is required for endodermal remodeling and lateral root initiation. We identify that MICROTUBULE ASSOCIATED PROTEIN 70-5 (MAP70-5) is necessary for the establishment of this spatially defined microtubule organization and endodermis remodeling and thus contributes to lateral root morphogenesis. We propose that MAP70-5 and cortical microtubule arrays in the endodermis integrate the mechanical signals generated by lateral root outgrowth, facilitating the channeling of organogenesis.